REMOVAL OF TEXTILE WASTEWATER OF DIRECT BLUE 14 DYES BY MODIFIED CHITOSAN AND MODIFIED CHITOSAN BENTONITE COMPOSITES - Septiani, Wulan
The content of dyes in textile waste threatens the survival of living things. One of the commonly used synthetic textile dyes is a direct dye. Direct blue 14 (DB 14) is widely used in dyeing fabrics, especially cotton, rayon, or wool, because it is easy to use and does not require special conditions. These synthetic dyes have an aromatic structure which difficult to biodegrade due to the formation of strong covalent bonds between the C atoms from dyes and the O, N, or S atoms of the hydroxy, amine, or thiol groups, therefore it needs processing before being discharged into the river. Among the methods commonly used in textile dye waste treatment, adsorption is a physical method that is in great demand because of its advantages: high efficiency, low cost, easy handling, as well as high availability and variety of adsorbents. By using chitosan crosslinked glutaraldehyde (KG) and chitosan-modified bentonite composite (KKGB), is expected to provide an alternative in removing textile dye waste, so it easily to applied by the textile industry players, especially cloth dyers. This study aims to use KG and KKGB as adsorbents for removing textile dye waste process then the results are measured by a UV-Vis spectrophotometer. The research methodology was a composite synthesis of chitosan and bentonite mixed with glutaraldehyde as a chitosan crosslink agent (KKGB), chitosan crosslinked glutaraldehyde without bentonite (KG) was also used. Both of KKGB and KG characterization was analyzed using SEM, XRD, and FTIR instruments. The condition of textile dyes adsorption were using adsorption parameter, such as variations in contact time (1-85 minutes), variations in adsorbent doses (0.1-2.0 g/L), variations in the initial concentration of DB 14 solution (1-35 mg/ L), variations in the pH initial of DB 14 solution (4-12), and variations in particle size (74-105 ?m). In addition, two kinetic models also determined, namely pseudo-first order and pseudo-second order and also adsorption isotherms using Langmuir and Freundlich. This research also carried out desorption experiments with various dissolving agents, such as NaCl, H2SO4, NaOH, EDTA, and distilled water. The results showed that the optimum conditions for both adsorbents were 20 minutes contact time; The optimum dose used is 1.4 g/L; and the optimum pH for KKGB and KG is 4. So these conditions are used in the adsorption application of textile dye waste DB 14. The kinetic model of KKGB and KG adsorbents uses pseudo second-order with a K2 value of 0.081 for KKGB and 0.060 for kgs. The GC adsorption equilibrium isotherm uses the Langmuir model with a coefficient of determination (R2) of 0.9992 for KKGB using the Freundlich model with an R2 of 0.9995. The two adsorbents showed good removal values for DB 14 textile dye waste, 97.36% for KKGB and 99.38% for KG. The result of FTIR spectra before and after the adsorption process showed the appearance of a new peak in KG at 1505 cm?1, it means the C-C group from benzene and at 1320 cm?1 due to the presence of the S-O group from DB 14. Whereas in KKGB is occurred the peak shift at 1485 to 1492 due to the stretching of the N-H groups, which means that there was an electrostatic interaction between the positive charge of the adsorbent and the anionic groups of the dye. Meanwhile, there was a shift at 915 cm-1 which means there was an interaction between the hydroxyl groups of adsorbent and sulfonic groups of the dye. This means the adsorption of DB 14 occurs because the interaction of the adsorbent surface with the solution rather than adsorben porosity. It can be concluded that the interaction occured between DB 14 and KKGB is a combination of adsorbent surface interactions, whereas in KG is a chemical force.